How Food Vlogger Content Influences Purchase Intention: A SEM Analysis of Audience Attitudes - Sulton Almadani; Yolanda Masnita; Husna Leila Husna (Manunggal Halim Jaya, 2026)
Food vloggers increasingly shape consumers’ dining and online purchase decisions, yet evidence on how audience attitudes translate into purchase intention remains mixed. This study examines how entertainment value, information value, and enjoyment influence consumer attitudes toward food videos and vloggers, and how these attitudes affect purchase intention. Drawing on Uses and Gratifications Theory, an online survey of 110 food vlog follower respondents was analyzed using Structural Equation Modeling (SEM) via AMOS. Results indicate that entertainment value enhances attitudes toward vloggers, while information value strengthens attitudes toward food videos. Enjoyment did not significantly affect attitudes toward videos, and information value did not significantly affect attitudes toward vloggers. Positive attitudes toward both videos and vloggers significantly increased purchase intention. The study highlights the importance of distinguishing between content and content creator evaluations in digital marketing. Practically, combining informative and entertaining content can enhance persuasive impact and audience trust. Future research should consider longitudinal, experimental, and diverse demographic approaches to improve generalizability.